2017
DOI: 10.2196/mhealth.8352
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Technology Use Across Age Groups in Patients Eligible for Cardiac Rehabilitation: Survey Study

Abstract: BackgroundEmerging evidence indicates mobile technology–based strategies may improve access to secondary prevention and reduce risk factors in cardiac patients. However, little is known about cardiac patients’ use of mobile technology, particularly for health reasons and whether the usage varies across patient demographics.ObjectiveThis study aimed to describe cardiac patients’ use of mobile technology and to determine variations between age groups after adjusting for education, employment, and confidence with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 27 publications
3
49
0
3
Order By: Relevance
“…It has also been suggested that technology training for older adults may need to be geared toward their needs and learning styles [ 44 , 45 ]. As older adults are less likely to use mobile technology than younger adults, interventions and training geared toward older adults may be necessary [ 46 ]. Together, this suggests that interventions for technology-facilitated CR should include opportunities for in-person training of participants on use of the technology, in addition to on-demand help.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that technology training for older adults may need to be geared toward their needs and learning styles [ 44 , 45 ]. As older adults are less likely to use mobile technology than younger adults, interventions and training geared toward older adults may be necessary [ 46 ]. Together, this suggests that interventions for technology-facilitated CR should include opportunities for in-person training of participants on use of the technology, in addition to on-demand help.…”
Section: Discussionmentioning
confidence: 99%
“…Formative research on older adults with chronic diseases is lacking, with only two studies investigating cardiac patients’ frequency of social media use [ 34 ], and experience and perceptions of using Facebook [ 35 ]. One study assessed how patients with T2DM communicate health information using Facebook [ 36 ].…”
Section: Development Implementation and Evaluation Of Facebook Groupmentioning
confidence: 99%
“…Therefore, generalisability of the study result cannot be assumed. In addition, while there is some evidence on technology readiness of people across different age groups, computer readiness among people with cardiac conditions is uncertain (Gallagher et al, 2017;Liu, Stroulia, Nikolaidis, Miguel-Cruz, & Rincon, 2016;Makkonen, Frank, & Koivisto, 2017). Refinement of the education app and subsequent testing of the app in a larger study is warranted.…”
Section: Limitationsmentioning
confidence: 99%